BENTUK PENDEKATAN KOMUNIKASI ORANG TUA DALAM MEMBERI PEMAHAMAN TAYANGAN TELEVISI PADA ANAK USIA SEKOLAH DASAR - Harnina Ridwan (Kanal: Jurnal Ilmu Komunikasi, 2013)
The Problem in this research is how the form of parent’s approach in guiding televisi shows on the elementary school aged children. This research was conducted in Rahandouna Sub district, Poasia District, Kendari. Determination of the location is due to consideration that most parents in Rahandouna have elementary school-aged children who love watching televisi, thus require efficient forms of communication in guiding telvisi shows on the children. This research uses qualitative method with twenty informants. The results showed that the form of the parent’s approach in guiding televisi shows on the elementary school aged children in Rahandouna, Poasia, Kendari consists of interpersonal communication approach which means giving meaning and views by doing direct communication to the children in order to provide better understanding of the positive and negative effects of the televisi shows that can also strengthen the affection between parents and children.